RESPON PEMBERIAN PUPUK UREA DAN PUPUK KCl TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI RAWIT (Capsicum frutescens L.) DALAM POLIBAG - Novilda Elizabeth Mustamu (UNIVERSITAS LABUHANBATU, 2019)
One of the factors that determine the quality of chilli pepper seedlings is fertility of growing of medium. Fertility of growing medium can be incrase with fertilization, by using of Urea fertilizer and of KCl fertilizer be expected to increase chilli pepper seedlings. This research was carried out in Dewi Sartika, Rantau Selatan Sub District of West Labuhanbatu, East of nort Sumatera Utara in March until June 2015 using randomize complete block design with two factors. The first factor used Urea fertilizer (0, 1.5, 2.5, 3gr/polibag), and the second factor used of KCl fertilizer (1, 2, 3gr/polibag). Parameter observed were plant height, stem diameter, weight of the fruit crop samples, and heavy fruit perplot. From the research of Urea fertilizer very significant effect on all parameters of KCl fertilizer very significant weight of the fruit crop samples and weight fruit/plot. Interaction of Urea fertilizer and KCl fertilizer significant weight of the fruit crop samples and very significant weight of fruit/plot. The result from this experimental were obtained in the treatment of Urea fertilizer Urea fertilizer application (U3) and of KCl fertilizer application (K3). Keywords : Urea fertilizer, KCl fertilizer, Chili pepper seedlings.